Investigating the fluctuations of solar and wind energy - M R Rahimi Tabar; A Madanchi; M R Absalan; M Anvari (Iranian Journal of Physics Research, 2019)
A time series study of the electrical energy generated by wind turbines and solar cells shows that the energy produced has a lot of fluctuations due to the geographic conditions. These ups and downs have caused not only the share of these sources to be marginal, but also they lead to the volatility of electric power plants. By examining several different data from different countries and regions with the frequency of second and minute, we show that different scale behaviors exist at different time intervals and reveal their other random and nonlinear characteristics. We also compare the non-Gaussian behavior of these regions together, showing that studying the properties of such data helps us to better measure the incidence of these energies